A half century of γ-aminobutyric acid. (November 2019) - Smart, Trevor G; Stephenson, F Anne
Γ-aminobutyric acid has become one of the most widely known neurotransmitter molecules in the brain over the last 50 years, recognised for its pivotal role in inhibiting neural excitability. It emerged from studies of crustacean muscle and neurons before its significance to the mammalian nervous system was appreciated. Now, after five decades of investigation, we know that most neurons are γ-aminobutyric-acid-sensitive, it is a cornerstone of neural physiology and dysfunction to γ-aminobutyric acid signalling is increasingly documented in a range of neurological diseases. In this review, we briefly chart the neurodevelopment of γ-aminobutyric acid and its two major receptor subtypes: the γ-aminobutyric acidA and γ-aminobutyric acidB receptors, starting from the humble invertebrate origins of being an 'interesting molecule' acting at a single γ-aminobutyric acid receptor type, to one of the brain's most important neurochemical components and vital drug targets for major therapeutic classes of drugs. We document the period of molecular cloning and the explosive influence this had on the field of neuroscience and pharmacology up to the present day and the production of atomic γ-aminobutyric acidA and γ-aminobutyric acidB receptor structures. γ-Aminobutyric acid is no longer a humble molecule but the instigator of rich and powerful signalling processes that are absolutely vital for healthy brain function.